Ultrastructural studies on the antennal sensilla of Pteromalus puparum L. (Hymenoptera: Pteromalidae) - XU Ying; HONG Jian; HU Cui (浙江大学学报. 农业与生命科学版)
Antennal surface structure of Pteromalus puparum L. was observed by scanning electron microscope. Seven types of sensilla, namely, thick-walled chemoreceptor, thin-walled chemoreceptor, plate organ, short-curved tactile hair, sharp-tipped tactile hair, basiconic capitate peg and chaeticum sensillum were found on the antennae both of female and male. The shape of these sensilla and their distribution were described, and their difference between sexes was discussed.